1977
DOI: 10.1163/156853977x00324
|View full text |Cite
|
Sign up to set email alerts
|

Play and Socio-Sexual Behaviour in a Captive Chimpanzee (Pan Troglodytes) Group

Abstract: Abstract1. Play and socio-sexual behaviors were studied in a captive chimpanzee group composed of three mothers and their offspring. 2. Mother-other infant relationships were more extensive and varied than those reported among wild chimpanzees. These relationships did not affect the motherinf ant bond. 3. Socio-sexual behaviors were regularly directed toward infants by all group members, including other infants. It is suggested that infant socio-sexuality should be viewed not only as a developmental phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…As reported earlier for captive (Hess, 1973;Hoff et al, 1978;Keiter & Pichette, 1979) and other wild gorillas (Harcourt et al, 1980(Harcourt et al, , 1981 such episodes of genital stimulation were initiated in the context of play, accompanied by intimate body contact and a generally heightened state of behavioral arousal, i.e., active wrestling, embracing, etc. Similar context-related genital stimulation has also been reported for immature common chimpanzees in the wild (Plooij, 1984;Tutin & McGinnis, 1981;van Lawick-Goodall, 1968) and in captivity (Savage & Malick, 1977). Bingham (1928), who conducted the first inquiry into sex-related behavior of immature common chimpanzees (in captivity), had not expected to see such behavior prior to maturity, e.g., "This copulatory play, years before reproductive maturity, is the most surprising behavior I have ever observed!"…”
Section: Discussionsupporting
confidence: 72%
“…As reported earlier for captive (Hess, 1973;Hoff et al, 1978;Keiter & Pichette, 1979) and other wild gorillas (Harcourt et al, 1980(Harcourt et al, , 1981 such episodes of genital stimulation were initiated in the context of play, accompanied by intimate body contact and a generally heightened state of behavioral arousal, i.e., active wrestling, embracing, etc. Similar context-related genital stimulation has also been reported for immature common chimpanzees in the wild (Plooij, 1984;Tutin & McGinnis, 1981;van Lawick-Goodall, 1968) and in captivity (Savage & Malick, 1977). Bingham (1928), who conducted the first inquiry into sex-related behavior of immature common chimpanzees (in captivity), had not expected to see such behavior prior to maturity, e.g., "This copulatory play, years before reproductive maturity, is the most surprising behavior I have ever observed!"…”
Section: Discussionsupporting
confidence: 72%
“…SAVAGE and MALICK (1977) found that the quality of play and grooming in a group of adolescents and one infant closely resembled behavior seen in the wild. Other similarities between wild and captive chimpanzees have been reported: qualitative descriptions of social displays (REYNOLDS & LUSCOMBE, 1976); sleeping patterns (RISS & GOODALL, 1976); and play in very young infants (NADLER & BRAGGIO, 1974).…”
Section: Introductionmentioning
confidence: 74%
“…The Washington Park Zoo (WPZ) chimpanzee collection was well suited for this study because it was an actively breeding group of long standing which included a fully mature male, three adult females, and three infants. Groups previously studied have not included a mature male (e.g., LEMMON, TEMMERLIN, & SAVAGE, 1975;SAVAGE & MALICK, 1977;MERRICK, 1977). Also, unlike other studied groups, the WPZ chimpanzees were housed in a small enclosure more typical of captive rearing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In non-human primates, avoidance of mat ing between relatives is often maintained by dispersal of mature males from natal groups [1,2], although active avoidance of motherson incestuous mating within a group has been reported for chimpanzees [3]. In fact, dispersal can enhance the reproductive suc cess of migrating males in two ways, either because the cost of inbreeding depression in curred by staying in the natal groups would exceed that of transferring or because emigra tion provides access to more oestrous females [4], Indeed, it has been suggested that the cause for male dispersal is competition for access to females [5,6], However, in red howl ers (Alouatta seniculus) and mantled howlers (A. palliata), both sexes are reported to dis perse routinely [7][8][9].…”
Section: Introductionmentioning
confidence: 99%